RecQ-like helicase 4 (RECQL4) exacerbates resistance to oxaliplatin in colon adenocarcinoma via activation of the PI3K/AKT signaling pathway. Issue 1 (1st January 2021) - Zhou, Fei; Wang, Leiming; Jin, Kangpeng; Wu, Yang
ABSTRACT: Oxaliplatin (OXA) resistance is a great challenge for colon adenocarcinoma (COAD) chemotherapy. The promoting role of RecQ-Like Helicase 4 (RECQL4) in chemoresistance to platinum-based drugs has been identified, whereas the effect and specific mechanism of RECQL4 in regulating OXA resistance within COAD have not been explicated yet. In this work, RECQL4 mRNA expression was detected by RT-qPCR. RECQL4, phosphorylated PI3K (p-PI3K), PI3K, phosphorylated AKT (p-AKT), and AKT protein expression were measured by western blotting. CCK-8, flow cytometry, wound healing, and transwell assays were utilized to analyze OXA resistance, cell proliferation, apoptosis, cell cycle, migration and invasion. Herein, we found RECQL4 was upregulated in COAD, especially in OXA-resistant COAD tissues and cells. RECQL4 overexpression facilitated proliferation and metastasis of OXA-resistant COAD cells; on the contrary, RECQL4 knockdown attenuated proliferative and metastatic capabilities in OXA-resistant COAD cells. Moreover, RECQL4 promoted OXA resistance in OXA-resistant COAD cells via activating the P13 K/AKT signaling. To sum up, the results suggest that RECQL4 depletion may be a crucial mechanism to reverse OXA resistance in COAD via inhibition of the P13 K/AKT pathway in vitro, thereby providing a novel target for overcoming OXA resistance in COAD.